2016
DOI: 10.1017/s2040174416000520
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between childhood growth parameters and adult blood pressure: the Fels Longitudinal Study

Abstract: Previous research has shown that childhood body size is associated with blood pressure in adulthood, and that early and rapid growth rates are correlated with adverse cardiovascular outcomes. Our objectives are to estimate associations between childhood body size growth parameters and adult blood pressure, and to examine the effect of early attainment of critical growth milestones on adult blood pressure, relative to normal or late attainment. Lifetime height and body mass index (BMI) measurements in childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…It has also been hypothesized that obesity during childhood affects growth [ 2 , 3 ]. Alterations in linear growth were reported to be associated with more adverse adult cardiovascular risk profile implying that advanced early linear growth is related to negative cardiovascular health outcomes such as coronary heart disease, even independently from body mass index (BMI) [ 4 , 5 ]. Furthermore, more detailed insight into the dynamic association between body weight and growth may contribute to the understanding of the complex relationships of energy balance, hormonal milieu, and growth in the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been hypothesized that obesity during childhood affects growth [ 2 , 3 ]. Alterations in linear growth were reported to be associated with more adverse adult cardiovascular risk profile implying that advanced early linear growth is related to negative cardiovascular health outcomes such as coronary heart disease, even independently from body mass index (BMI) [ 4 , 5 ]. Furthermore, more detailed insight into the dynamic association between body weight and growth may contribute to the understanding of the complex relationships of energy balance, hormonal milieu, and growth in the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that BMI changes rapidly in childhood [16]. Recent evidence has suggested that there are varied BMI changing patterns among children, which may bring different health outcomes [17][18][19]. BMI measurements in the majority of existed epidemiological studies were just be performed at one or limited occasions [20,21], which may be insufficient to explain the risk of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, birth weight, early height growth and early BMI growth were each associated with higher blood pressure in adulthood, and greater weight gain throughout childhood has been associated with greater adult adiposity. 3,38,39 Studies in a series of low and middle-income countries (LMICs), including South Africa, illustrated associations between both lower birth weight and increased weight gain after age 2 years with higher adult glucose intolerance. 4 Our study suggests that while increased growth from age 2 to 5 years may be associated with greater risk of multiple morbidities as expressed through high AL score, there is not a consistent association between early growth (0-2 years) and increased morbidity in early adulthood.…”
Section: Discussionmentioning
confidence: 99%